Acupuncture for Histamine-Induced Itch: Association With Increased Parasympathetic Tone and Connectivity of Putamen-Midcingulate Cortex - Min, Seorim; Kim, Koh-Woon; Jung, Won-Mo; Lee, Min-Jung; Kim, Yu-Kang; Chae, Younbyoung; Lee, Hyangsook; Park, Hi-Joon (Frontiers in Neuroscience, 2019)
Previous studies have suggested that acupuncture is effective for ameliorating itch intensity. However, factors associated with the antipruritic effects of acupuncture have yet to be clarified. In a randomized, sham-controlled, crossover trial, we investigated the antipruritic effects of acupuncture against histamine-induced itch in healthy volunteers. Autonomic changes using heart rate variability (HRV) and brain connectivity using functional magnetic resonance imaging (fMRI) were also assessed to identify physiological factors associated with the acupuncture response. Acupuncture significantly reduced itch intensity and skin blood perfusion as assessed by laser Doppler perfusion imaging compared to sham control, indicating the antipruritic effects of acupuncture. In responder and nonresponder analysis, the power of normalized high frequency (HF norm) was significantly higher, while the power of normalized low frequency (LF norm) and LF/HF ratio were significantly lower in responders compared to nonresponders, suggesting the acupuncture response involved parasympathetic activation. In fMRI analysis, the putamen and the posterior part of the midcingulate cortex (pMCC) were positively connected to itch and negatively correlated with itch intensity in responders. These results suggest that parasympathetic activity and functional connectivity of the putamen and pMCC could be associated with antipruritic response to acupuncture.